Compensatory effects of curcumin on cisplatin-induced toxicity in rabbit testis - Kandemir, F. M.; Benzer, F.; Yildirim, N. C.; Ozdemir, N. (Academic Journals, 2011)
Curcumin, a widely used spice and colouring agent in food, has been shown to possess potent antioxidant, antitumor promoting and anti-inflammatory properties in vitro and in vivo. The present study was designed to investigate the protective effects of curcumin on changes in the levels of lipid peroxidation and endogenous antioxidants induced by cisplatin (cis-diamminedichloroplatinum II, CDDP) in the testiclular tissue of rabbits. 18 healthy male New Zealand white rabbits were equally divided into three groups of six rabbits each, control, cisplatin, and cisplatin+curcumin. The degree of protection produced by cisplatin was evaluated by determining the level of malondialdehyde (MDA) and glutathione (GSH), the activity of catalase (CAT), glutathione peroxidase (GSH-Px), were estimated from testes homogenates. MDA levels were increased with cisplatin compared to control but in cisplatin+curcumin group, MDA levels were found to be lower than cisplatin group (p<0.05). The activity of CAT and GSH-P-X was decreased in cisplatin and cisplatin+curcumin groups compared to control (p<0.05). In the case of cisplatin+curcumin CAT and GSH-Px activity were increased compared to cisplatin group (p<0.05). GSH levels were decreased with cisplatin but administration cisplatin+curcumin increased the levels of GSH comared to cisplatin group (p<0.05). In the present study, co-administration of curcumin with cisplatin prevented the damage to testes induced by this drug and may be considered as a potentially useful candidate in the combination chemotherapy with cisplatin.
Keywords: Rabbit; cisplatin; curcumin; testes; oxidative stress